Population connectivity of fan-shaped sponge holobionts in the deep Cantabrian Sea. (January 2021) - Busch, Kathrin; Taboada, Sergi; Riesgo, Ana; Koutsouveli, Vasiliki; Ríos, Pilar; Cristobo, Javier; Franke, Andre; Getzlaff, Klaus; Schmidt, Christina; Biastoch, Arne; Hentschel, Ute
Abstract: Connectivity is a fundamental process driving the persistence of marine populations and their adaptation potential in response to environmental change. In this study, we analysed the population genetics of two morphologically highly similar deep-sea sponge clades ( Phakellia hirondellei and the 'Topsentia-and-Petromica' clade, (hereafter referred to as 'TaP clade')) at three locations in the Cantabrian Sea and simultaneously assessed the corresponding host microbiome by 16S rRNA gene sequencing. A virtual particle tracking approach (Lagrangian modelling) was applied to assess oceanographic connectivity in the study area. We observed overall genetic uniformity for both sponge clades. Notably, subtle genetic differences were observed for sponges of the TaP clade and also their microbiomes between a canyon and bank location, < 100 km apart and with the same depth range. The Lagrangian model output suggests a strong retention of larvae in the study area with variable inter-annual connectivity via currents between the three sampling regions. We conclude that geologic features (canyons) and the prevailing ocean currents may dictate sponge holobiont connectivity and that differentiation can emerge even on small spatial scales. Highlights: Fan-shaped sponges display panmixia at three locations in the Cantabrian Sea. Subtle sponge population genetic and pronounced microbial differences were observed between a canyon and bank (<100km apart). Lagrangian modelling reveals variable inter-annual connectivity via ocean currents between the sampling regions. Interdisciplinary approaches can help to improve understanding about connectivity in the deep-sea.